A low thermal conductivity, high temperature resistant silicon oxide aerogel insulation felt and preparation method thereof

By using low-thermal conductivity, high-temperature resistant silicon oxide aerogel thermal insulation felt prepared by 15nm-45nm silica sol and polyethyl silicate, the existing silicon oxide aerogel thermal insulation felt has been solved, and excellent thermal insulation performance and tensile strength at high temperatures are achieved.

CN119569418BActive Publication Date: 2025-04-18CHANGSHA RONGLAN MACHINERY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510125958.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-18
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

The existing silicon oxide aerogel insulating felt has poor stability at high temperatures, insufficient infrared radiation shading capacity, and rapid thermal conductivity, making it difficult to meet the needs of high temperature use.

Method used

A low-thermal conductivity, high-temperature resistant silicon oxide aerogel heat insulating felt was prepared by mechanical stirring and microwave heating, and the powder was modified through silicon source hydrolysate to improve powder dispersion and stability.

Benefits of technology

The temperature resistance of the silicon oxide aerogel heat insulation felt is achieved at 1100℃, the thermal conductivity remains excellent at high temperatures, and the tensile strength is high. It is suitable for aerospace, aerospace and industrial kilns and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569418B_ABST
    Figure CN119569418B_ABST
Patent Text Reader

Abstract

The invention discloses a low thermal conductivity, high temperature resistant silica aerogel insulation felt and a preparation method thereof. The silica aerogel felt prepared by the invention has the characteristics of temperature resistance of 1100°C, good flexibility, excellent high temperature insulation performance and easy construction, and has broad application prospects in aerospace, industrial kilns and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel thermal insulation materials, and specifically relates to a low thermal conductivity, high temperature resistant silica aerogel thermal insulation felt and a preparation method thereof. Background Art

[0002] Aerogel is a nanoporous material with the characteristics of low density, low thermal conductivity, and high specific surface area. It is the solid material with the lowest thermal conductivity at room temperature. At present, silica aerogel insulation felt is widely used in oil pipelines, thermal networks, nuclear power, storage tank equipment, tank armor, rail transit, ships and other fields. However, the silica aerogel insulation felt prepared by the existing method has poor high-temperature stability, and the long-term use temperature is not higher than 650°C, which cannot meet the use requirements at higher temperatures. In addition, silica aerogel has strong permeability to near-infrared thermal radiation with a wavelength of 3-8μm, so it has poor shielding ability against infrared radiation at high temperatures, and the thermal conductivity rises rapidly. The temperature resistance and high-temperature thermal insulation performance of silica aerogel composite materials need to be improved. Although alumina aerogel has good high-temperature resistance, it will undergo phase change when the temperature rises, especially above 1000°C, resulting in a significant decrease in the specific surface area of ​​alumina aerogel, which limits its application.

[0003] In order to improve the thermal insulation performance of silica aerogel at high temperatures, a sunscreen is usually added to the silica aerogel to improve its infrared radiation shielding ability and improve its high-temperature thermal insulation ability. Commonly used infrared sunscreens include carbon black, TiO 2 Powder, B 4 C powder, SiC particles, etc. Since the density of the sunscreen agent is quite different from that of the sol, there are problems of uneven dispersion and agglomeration when added to the sol, resulting in unstable improvement effect. Even if ultrasonic method or surfactant addition method is used, the effect is not obvious. For example, Chinese patent announcement No. CN 114804819 B discloses a high-temperature resistant aerogel composite material and its preparation method, which uses chemical vapor infiltration method to evenly compound the sunscreen agent on the substrate, and then compound it with the silica sol to which the sunscreen agent is added, and after drying, a high-temperature resistant silica aerogel composite material is obtained. However, this method is costly and not suitable for mass production. Summary of the invention

[0004] In view of the problem that in the prior art, sunscreen agents are added to silica aerogels, but the sunscreen agents have a large difference in density from the sol, and are unevenly dispersed and agglomerated when added to the sol, resulting in unstable improvement effects. The present invention provides a low thermal conductivity, high temperature resistant silica aerogel insulation felt and a preparation method thereof. The silica aerogel felt prepared by the present invention has the characteristics of temperature resistance of 1100°C, good flexibility, excellent high temperature insulation performance, and easy construction, and has broad application prospects in aerospace, industrial kilns and other fields.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0007] S1: Sol configuration:

[0008] S1-1, component A: ethanol solution monodispersed silica sol with polyethyl silicate, acid catalyst, H 2 O is stirred evenly and fully hydrolyzed to obtain a silicon-based hydrolyzate;

[0009] The particle size of the monodispersed silica sol in the ethanol solution is 15nm-45nm, and the solid content is 10%-30%; the acid catalyst is one of hydrochloric acid, oxalic acid, nitric acid, sulfuric acid, acetic acid, and hydrofluoric acid, the concentration of the acid catalyst solution is 0.01mol / L-0.8mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethylsiloxane, acid catalyst, H 2 The mass ratio of O is 1:(0.02-1):(0.001-0.1):(0.20-1.5);

[0010] S1-2, component B: mix anhydrous ethanol and concentrated aqueous ammonia evenly to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1:(0.002-0.08);

[0011] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 4.5-6, add the pre-treated sunscreen, and mix evenly by mechanical stirring + passing compressed air at the bottom of the container to obtain a mixed powder;

[0012] The organic silicon source is one of ethyl orthosilicate, methyl orthosilicate, methyl triethoxysilane, methyl trimethoxysilane, and polyethyl silicate; wherein the organic silicon source: anhydrous ethanol: H 2 O weight ratio is 1: (10-20): (2-6); the sunscreen is one of silicon carbide, titanium dioxide, and zirconium oxide; the ratio of the sunscreen to the sol in component C is (0.5-3) kg: 100L, and the powder particle size is 1 μm-6 μm; the sol is an organic silicon source + ethanol + H 2 O+inorganic acid;

[0013] The pretreatment method of the mixed powder is:

[0014] S1-3-1, rinsing: rinse with anhydrous ethanol 1 to 3 times;

[0015] S1-3-2, surface treatment: hydroxylation or alkylation treatment is performed on the powder surface, and the powder is soaked in a surface treatment solution for 24 hours;

[0016] The surface treatment solution is one of 1wt%-5wt% NaOH solution and 20wt%-50wt% methyl orthosilicate solution;

[0017] S2: prepare a whole roll of fiber felt: width 0.5m-1.5m;

[0018] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the volume fraction of quartz fiber in the total fiber is 5%-15%;

[0019] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:(2-8):(0.5-2) and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0020] S4: transporting the wet gel felt obtained in the above step to a microwave cavity through a transport line for microwave heating for rapid gelation and curing, and maintaining the temperature in the microwave cavity at 40° C.-60° C.;

[0021] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 4h-12h;

[0022] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0023] S7: After supercritical drying of the replaced wet gel felt, a low thermal conductivity, high temperature resistant silica aerogel insulation felt is obtained. The obtained low thermal conductivity, high temperature resistant silica aerogel insulation felt has the following properties:

[0024] The maximum operating temperature reaches 1100℃, and the thickness shrinkage rate after treatment at 1100℃ for 1h is 0.20%-1.82%;

[0025] The typical value of thermal conductivity at 800℃ is 0.048W / (m·K)-0.054W / (m·K), the typical value of thermal conductivity at 1000℃ is 0.066W / (m·K)-0.072W / (m·K), and the typical value of thermal conductivity at 1100℃ is 0.076W / (m·K)-0.085W / (m·K);

[0026] Tensile strength is 0.32MPa-0.45MPa;

[0027] The 30mm thick silica aerogel insulation felt was heated on one side at 1100℃ for 3600s, and the cold side temperature was less than 200℃.

[0028] Furthermore, the hydrolysis time in step S1-1 is 2h-8h.

[0029] Furthermore, the uniform mixing in step S1-2 is carried out by stirring for 10 min to 20 min.

[0030] Furthermore, the mixing in step S1-3 is uniform and the stirring time is 2h-8h.

[0031] Furthermore, the rapid gelation described in step S4 refers to a gelation time of 2 min to 6 min.

[0032] Furthermore, the supercritical drying in step S7 is CO 2 Supercritical drying or ethanol supercritical drying, CO 2 The supercritical drying process is as follows: aerogel is dried in CO 2 Under the protection of gas, the drying temperature is 40℃-75℃, the pressure of the autoclave is controlled at 8MPa-20MPa, and the reaction time is 4h-24h; the supercritical drying process of ethanol is: the aerogel is protected by nitrogen gas, the drying temperature is 260℃-320℃, the pressure of the autoclave is controlled at 8MPa-14MPa, and the reaction time is 4h-10h.

[0033] The present invention also relates to a low thermal conductivity, high temperature resistant silica aerogel insulation felt, which is obtained by using the above-mentioned preparation method of a low thermal conductivity, high temperature resistant silica aerogel insulation felt and has the following properties:

[0034] The maximum operating temperature reaches 1100℃, and the thickness shrinkage rate after treatment at 1100℃ for 1h is 0.20%-1.82%;

[0035] The typical value of thermal conductivity at 800℃ is 0.048W / (m·K)-0.054W / (m·K), the typical value of thermal conductivity at 1000℃ is 0.066W / (m·K)-0.072W / (m·K), and the typical value of thermal conductivity at 1100℃ is 0.076W / (m·K)-0.085W / (m·K);

[0036] Tensile strength is 0.32MPa-0.45MPa;

[0037] The 30mm thick silica aerogel insulation felt was heated on one side at 1100℃ for 3600s, and the cold side temperature was less than 200℃.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] 1. The existing silica aerogel has a particle skeleton of usually 2-5nm. Although the thermal conductivity is low, long-term use will cause the temperature not to exceed 650℃. If you want to increase the use temperature of silica aerogel, you can thicken the particle skeleton, but the thickening of the particle skeleton will lead to an increase in thermal conductivity. The preparation method of a low thermal conductivity, high temperature resistant silica aerogel insulation felt described in the present invention uses a 15nm-45nm silica sol to prepare an aerogel. The particle skeleton usually reaches tens of nanometers, while the aerogel particle skeleton prepared by polyethyl silicate as a silicon source is a few nanometers. Therefore, the aerogel prepared by both as silicon sources has large particles and small particles separated, which can improve the temperature resistance of the aerogel while still maintaining excellent thermal conductivity. At the same time, when the particle size of silica aerogel increases, it becomes increasingly difficult to achieve rapid gelation. The introduction of polyethyl silicate, a highly active silicon source, can be used as a gel initiator to promote the rapid gelation of silica aerogel with large particle size.

[0040] 2. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt described in the present invention can improve the temperature resistance of silica aerogel while improving the high temperature thermal conductivity of the aerogel insulation felt by controlling the content of the sunscreen.

[0041] 3. The current powder surface treatment technology is to modify the powder through a surfactant, but this method does not significantly improve the powder sedimentation and cannot achieve stable batch production. The preparation method of a low thermal conductivity, high temperature resistant silica aerogel insulation felt described in the present invention uses an organic silicon source hydrolyzate as a modifier, and the organic silicon source is dehydrated and condensed on the surface of the surface treated powder to form a silicon dioxide film, which surrounds the powder to achieve the effect of powder dispersion;

[0042] The current powder dispersion process usually adopts stirring and ultrasonic vibration to disperse. The preparation method of a low thermal conductivity, high temperature resistant silica aerogel insulation felt described in the present invention adopts mechanical stirring + bottom compressed air introduction, which can effectively prevent the powder from settling due to the large density difference with the solvent; after the fiber and the sol are mixed, the present invention adopts microwave drying to accelerate the rapid gelation of the sol to prevent the powder from settling during the gelation process.

[0043] 4. The ceramic fiber felts currently on the market are usually aluminum silicate fiber felts and mullite fiber felts. Because ceramic fibers are relatively brittle, the fiber felts will be damaged to a certain extent when the fibers are soaked in sol. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt described in the present invention uses ceramic fibers and quartz fibers to blend, utilizes the toughness of quartz fibers, improves the overall tensile strength of the fiber felt, and is conducive to the batch and stable preparation of aerogel insulation felts. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0045] Figure 1 This is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 2;

[0046] Figure 2 This is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 1 before heat treatment at 1100°C;

[0047] Figure 3 This is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 1 after heat treatment at 1100°C;

[0048] Figure 4 This is a SEM image of the low thermal conductivity, high temperature resistant silica aerogel prepared in Example 1;

[0049] Figure 5 This is a flow chart for preparing the low thermal conductivity, high temperature resistant silica aerogel insulation felt of the present invention. DETAILED DESCRIPTION

[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] like Figure 5 As shown, it is a flow chart of the preparation of low thermal conductivity, high temperature resistant silica aerogel insulation felt in the following embodiments;

[0052] Embodiment 1:

[0053] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0054] S1: Sol configuration:

[0055] S1-1, component A: ethanol solution monodispersed silica sol and polyethyl silicate, hydrochloric acid, H 2 O was stirred evenly and hydrolyzed for 6 h to obtain a silicon-based hydrolyzate;

[0056] The average particle size of the monodispersed silica sol in the ethanol solution is 30 nm, and the solid content is 20%; the acid catalyst is hydrochloric acid, the concentration of the acid catalyst solution is 0.5 mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethyl silicate, acid catalyst, H2 The mass ratio of O is 1:0.2:0.02:0.4;

[0057] S1-2, component B: stir anhydrous ethanol and concentrated aqueous ammonia for 20 minutes to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1:0.01;

[0058] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 4.5, add the sunscreen, and mix evenly by mechanical stirring + passing compressed air through the bottom of the container for 2 hours;

[0059] The organic silicon source is ethyl orthosilicate; wherein the organic silicon source: anhydrous ethanol: H 2 The weight ratio of O is 1:10:3; the sunscreen is titanium dioxide; the ratio of the sunscreen to the sol in component C is 1kg:100L, and the powder particle size is 1μm;

[0060] The pretreatment method of the mixed powder is:

[0061] S1-3-1, rinsing: rinse with anhydrous ethanol 3 times;

[0062] S1-3-2, surface treatment: soak the powder in 5wt% NaOH solution for 24h;

[0063] S2: prepare a full roll of fiber felt: width 1.5m;

[0064] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the quartz fiber accounts for 5% of the total fiber volume fraction;

[0065] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:5:0.5 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0066] S4: transporting the wet gel felt obtained in the previous step to a microwave cavity through a transport line for microwave heating for a rapid gel time of 4 minutes and curing, and maintaining the temperature in the microwave cavity at 45°C;

[0067] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 8 hours;

[0068] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0069] S7: The replaced wet gel felt is subjected to supercritical ethanol drying, and the process is as follows: the aerogel is protected by nitrogen gas, the drying temperature is 260°C, the pressure of the autoclave is controlled at 14 MPa, and the reaction time is 6 hours.

[0070] Embodiment 2:

[0071] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0072] S1: Sol configuration:

[0073] S1-1, component A: ethanol solution monodispersed silica sol and polyethyl silicate, hydrochloric acid, H 2 O was stirred evenly and hydrolyzed for 8 h to obtain a silicon-based hydrolyzate;

[0074] The average particle size of the monodispersed silica sol in the ethanol solution is 20 nm, and the solid content is 30%; the acid catalyst is nitric acid, the concentration of the acid catalyst solution is 0.02 mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethyl silicate, acid catalyst, H 2 The mass ratio of O is 1:0.5:0.1:1;

[0075] S1-2, component B: stir anhydrous ethanol and concentrated aqueous ammonia for 20 minutes to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1:0.02;

[0076] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 5.5, add the sunscreen, and mix evenly by mechanical stirring + passing compressed air through the bottom of the container for 4 hours;

[0077] The organosilicon source is methyltrimethoxysilane; wherein the organosilicon source: anhydrous ethanol: H 2 The weight ratio of O is 1:20:2; the sunscreen is silicon carbide; the ratio of the sunscreen to the sol in component C is 2kg:100L, and the powder particle size is 4μm;

[0078] The pretreatment method of the mixed powder is:

[0079] S1-3-1, rinsing: rinse with anhydrous ethanol 3 times;

[0080] S1-3-2, surface treatment: soak the powder in 20wt% methyl orthosilicate ethanol solution for 24h;

[0081] S2: prepare a full roll of fiber felt: width 1.5m;

[0082] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the quartz fiber accounts for 15% of the total fiber volume fraction;

[0083] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:4:1 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0084] S4: transporting the wet gel felt obtained in the previous step to the microwave cavity through a transport line for microwave heating with a rapid gel time of 2 minutes and curing, and maintaining the temperature in the microwave cavity at 60°C;

[0085] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 4 hours;

[0086] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0087] S7: The replaced wet gel felt is subjected to supercritical ethanol drying, and the process is as follows: the aerogel is protected by nitrogen gas, the drying temperature is 290°C, the pressure of the autoclave is controlled at 8MPa, and the reaction time is 4h.

[0088] like Figure 1 Shown is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 2.

[0089] Embodiment 3:

[0090] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0091] S1: Sol configuration:

[0092] S1-1, component A: ethanol solution monodispersed silica sol and polyethyl silicate, hydrochloric acid, H 2 O was stirred evenly and hydrolyzed for 2 h to obtain a silicon-based hydrolyzate;

[0093] The average particle size of the monodispersed silica sol in the ethanol solution is 45 nm, and the solid content is 10%; the acid catalyst is sulfuric acid, the concentration of the acid catalyst solution is 0.01 mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethyl silicate, acid catalyst, H 2 The mass ratio of O is 1:0.02:0.06:0.5;

[0094] S1-2, component B: stir anhydrous ethanol and concentrated aqueous ammonia for 10 minutes to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1: 0.002;

[0095] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 6, add the sunscreen, and mix evenly by mechanical stirring + passing compressed air through the bottom of the container for 8 hours;

[0096] The organosilicon source is methyltriethoxysilane; wherein the organosilicon source: anhydrous ethanol: H 2 The weight ratio of O is 1:15:6; the sunscreen is zirconium dioxide; the ratio of the sunscreen to the sol in component C is 0.5kg:100L, and the powder particle size is 2μm;

[0097] The pretreatment method of the mixed powder is:

[0098] S1-3-1, rinsing: rinse with anhydrous ethanol 3 times;

[0099] S1-3-2, surface treatment: soak the powder in 1wt% NaOH solution for 24h;

[0100] S2: prepare a full roll of fiber felt: width 0.5m;

[0101] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the quartz fiber accounts for 8% of the total fiber volume fraction;

[0102] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:8:2 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0103] S4: transporting the wet gel felt obtained in the previous step to the microwave cavity through a transport line for microwave heating with a rapid gel time of 3 minutes and curing, and maintaining the temperature in the microwave cavity at 40°C;

[0104] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 12 hours;

[0105] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0106] S7: The replaced wet gel felt is subjected to supercritical ethanol drying, and the process is as follows: the aerogel is protected by nitrogen gas, the drying temperature is 320°C, the pressure of the autoclave is controlled at 8MPa, and the reaction time is 10h.

[0107] Embodiment 4:

[0108] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0109] S1: Sol configuration:

[0110] S1-1, component A: ethanol solution monodispersed silica sol and polyethyl silicate, hydrochloric acid, H 2 O was stirred evenly and hydrolyzed for 4 h to obtain a silicon-based hydrolyzate;

[0111] The average particle size of the monodispersed silica sol in the ethanol solution is 15 nm, and the solid content is 25%; the acid catalyst is hydrofluoric acid, the concentration of the acid catalyst solution is 0.8 mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethyl silicate, acid catalyst, H 2 The mass ratio of O is 1:0.6:0.001:1.5;

[0112] S1-2, component B: stir anhydrous ethanol and concentrated aqueous ammonia for 20 minutes to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1:0.08;

[0113] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 4.5, add the sunscreen, and mix evenly by mechanical stirring + passing compressed air through the bottom of the container for 6 hours;

[0114] The organic silicon source is polyethyl silicate; wherein the organic silicon source: anhydrous ethanol: H 2 The weight ratio of O is 1:10:5; the sunscreen is titanium dioxide; the ratio of the sunscreen to the sol in component C is 1.5kg:100L, and the powder particle size is 6μm;

[0115] The pretreatment method of the mixed powder is:

[0116] S1-3-1, rinsing: rinse with anhydrous ethanol 3 times;

[0117] S1-3-2, surface treatment: soak the powder in 3wt% NaOH solution for 24h;

[0118] S2: prepare a full roll of fiber felt: width 1.5m;

[0119] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the quartz fiber accounts for 6% of the total fiber volume fraction;

[0120] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:2:0.5 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0121] S4: transporting the wet gel felt obtained in the previous step to a microwave cavity through a transport line for microwave heating for a rapid gel time of 6 minutes and curing, and maintaining the temperature in the microwave cavity at 40°C;

[0122] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 10 hours;

[0123] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0124] S7: The replaced wet gel felt is subjected to CO 2 Supercritical drying process: the aerogel is protected by nitrogen gas, the drying temperature is 75°C, the autoclave pressure is controlled at 16MPa, and the reaction time is 12h.

[0125] Embodiment 5:

[0126] A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt comprises the following steps:

[0127] S1: Sol configuration:

[0128] S1-1, component A: ethanol solution monodispersed silica sol and polyethyl silicate, hydrochloric acid, H 2 O was stirred evenly and hydrolyzed for 5 h to obtain a silicon-based hydrolyzate;

[0129] The average particle size of the monodispersed silica sol in the ethanol solution is 35 nm, and the solid content is 20%; the acid catalyst is oxalic acid, the concentration of the acid catalyst solution is 0.1 mol / L, and the solvent is anhydrous ethanol; wherein the silica sol, polyethyl silicate, acid catalyst, H 2 The mass ratio of O is 1:1:0.002:0.2;

[0130] S1-2, component B: stir anhydrous ethanol and concentrated aqueous ammonia for 20 minutes to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated aqueous ammonia is 1:0.06;

[0131] S1-3, C component: organic silicon source, anhydrous ethanol, H 2 After fully mixing, slowly add the acid catalyst, adjust the pH value of the solution to 6, add the sunscreen, and mix evenly by mechanical stirring + passing compressed air through the bottom of the container for 5 hours;

[0132] The organic silicon source is methyl orthosilicate; wherein the organic silicon source: anhydrous ethanol: H 2 The weight ratio of O is 1:20:5; the sunscreen is zirconium dioxide; the ratio of the sunscreen to the sol in component C is 3kg:100L, and the powder particle size is 1μm;

[0133] The pretreatment method of the mixed powder is:

[0134] S1-3-1, rinsing: rinse with anhydrous ethanol 3 times;

[0135] S1-3-2, surface treatment: soak the powder in 50wt% methyl orthosilicate ethanol solution for 24h;

[0136] S2: prepare a full roll of fiber felt: width 1.5m;

[0137] The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the quartz fiber accounts for 10% of the total fiber volume fraction;

[0138] S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:7:0.6 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt;

[0139] S4: transporting the wet gel felt obtained in the previous step to the microwave cavity through a transport line for microwave heating with a rapid gel time of 4 minutes and curing, and maintaining the temperature in the microwave cavity at 55°C;

[0140] S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 8 hours;

[0141] S6: adding ethanol to replace the wet gel felt after aging at room temperature;

[0142] S7: The replaced wet gel felt is subjected to CO 2 Supercritical drying process: the aerogel is protected by nitrogen gas, the drying temperature is 40°C, the autoclave pressure is controlled at 20MPa, and the reaction time is 24h.

[0143] Comparative Example 1:

[0144] The difference between Comparative Example 1 and Example 1 is that the average particle size of the particles in step S1-1 is 5 nm silica sol, and the rest is the same as Example 1.

[0145] Comparative Example 2:

[0146] The difference between Comparative Example 2 and Example 1 is that polyethyl silicate is not added in step S1-1, and the rest is the same as Example 1.

[0147] Comparative Example 3:

[0148] The difference between Comparative Example 3 and Example 1 is that in step S1-3, component C uses a surfactant to treat the sunscreen agent, and the rest is the same as Example 1.

[0149] Comparative Example 4:

[0150] The difference between Comparative Example 4 and Example 1 is that the fiber felt in step S2 is a ceramic fiber felt, and the rest is the same as Example 1.

[0151] Comparative Example 5:

[0152] The difference between Comparative Example 5 and Example 1 is that no sunscreen is added in step S1-3, and the rest is the same as Example 1.

[0153] Performance Test:

[0154] The thermal insulation felts prepared in the examples and comparative examples were subjected to performance tests:

[0155] Room temperature thermal conductivity test: Tested according to GB / T10295-2008.

[0156] 800℃ / 1000℃ / 1100℃ thermal conductivity test: Tested according to YB / T 4130-2005.

[0157] Tensile strength test: Tested according to GB / T17911-2018.

[0158] The results are shown in Table 1:

[0159] Table 1: Thermal insulation felt performance test table

[0160]

[0161] A roll (30 m2) of low thermal conductivity and high temperature resistant aerogel insulation felt obtained in Example 1 and Comparative Example 3 was placed in a container. 2 ) Randomly select 3 groups of samples, and test the properties of the composite materials as shown in Table 2:

[0162] Table 2: Thermal insulation felt performance stability test table

[0163]

[0164] Results and Discussion:

[0165] By comparing the embodiment with comparative example 1, the composite material prepared in comparative example 1 was heat treated at 1100°C for 1h, and the thickness shrinkage rate reached 10.52%. Due to the large shrinkage of the aerogel at high temperature, the thermal conductivity at 1000°C / 1100°C increased sharply. Figure 2 This is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 1 before heat treatment at 1100°C; Figure 3 This is a photograph of the low thermal conductivity, high temperature resistant silica aerogel insulation felt prepared in Example 1 after heat treatment at 1100°C; Figure 2 and Figure 3 As shown, the composite material prepared in Example 1 has no change in appearance before and after heat treatment at 1100° C. for 1 h, and the thickness shrinkage is only 0.55%. Figure 4This is a SEM image of the low thermal conductivity, high temperature resistant silicon oxide aerogel prepared in Example 1. Figure 4 As shown, the particle size of the large silica particles is about 30 nm, indicating that the aerogel particles prepared with large-sized silica have a larger skeleton, which improves the temperature resistance of the material.

[0166] By comparing the embodiment with comparative example 2, the thermal conductivity of the composite material prepared in comparative example 2 is higher. This is because the large-sized silica sol is difficult to achieve rapid gelation without adding a highly active silicon source such as polyethyl silicate. The long gelation time will aggravate the sedimentation of the sunscreen agent, resulting in unstable high-temperature performance of the composite material. However, the embodiment in which polyethyl silicate is added can achieve rapid gelation of the sol, and at the same time introduce small-particle silica aerogel, thereby Figure 4 It can be seen that the small-particle silica aerogel has a particle size of about 5 nm, which alternates with the large-sized silica aerogel (particle size of about 30 nm), making the thermal conductivity of the composite material excellent and stable.

[0167] By comparing Example 1 and Comparative Example 3 shown in Table 2, the performance of the samples in the example is stable, while in Comparative Example 3, a material with excellent thermal conductivity can be prepared by modifying the powder with a surfactant, but the performance stability of the prepared material is poor. This is because the powder still has sedimentation phenomenon after the traditional powder modification, resulting in uneven distribution of the powder inside the material. In Example 1, ethanol is used to soak and remove the residual organic matter in the powder, and then the surface is hydroxylated to make more hydroxyl groups on the surface of the powder. Then, an organic silicon source hydrolyzate is used as a modifier, and the organic silicon source is hydrolyzed and dehydrated and condensed with the hydroxyl groups on the surface of the powder. At the same time, the organic silicon sources are dehydrated and condensed, so a silicon dioxide film is formed on the surface of the powder to surround the powder and prevent the powder from agglomerating. At the same time, the embodiment combines mechanical stirring + bottom compressed air to disperse the powder, which can effectively prevent the powder from settling due to the large density difference with the solvent; ultrasound is performed in the ultrasonic dipping pool during the mixing process, which can effectively prevent the powder from settling during the dipping process; after the fiber and the sol are mixed, the wet gel is heated in a microwave cavity to promote the rapid gelation of the wet gel felt, which can prevent the powder from settling during the gelation process. The original powder surface modification method, dispersion process, and preparation process of the present invention can promote the uniform dispersion of the powder in the aerogel felt, thereby obtaining an aerogel insulation felt with stable performance.

[0168] By comparing the embodiment with comparative example 4, in the embodiment, quartz fiber is added to the ceramic fiber for blending, and the thickness shrinkage rate (1100°C, 1h) of the composite material is increased from 0.10% to 0.55%, but the tensile strength is also significantly enhanced (from 0.21MPa to 0.32MPa), and the fiber felt is not easily damaged during the material preparation process, which is suitable for mass production.

[0169] By comparing the embodiment with comparative example 5, the embodiment adds a sunscreen, has a low thickness shrinkage rate (1100°C, 1h), and has excellent high-temperature thermal conductivity. Compared with the comparative example, the thermal conductivity at 1100°C is reduced by about 50%, indicating that the addition of the sunscreen in the embodiment improves the temperature resistance of the material and can also significantly improve the high-temperature thermal insulation performance.

[0170] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt, characterized in that: The following steps are involved: S1: Sol configuration: S1-1, component A: using ethanol solution to disperse silica sol, polyethyl silicate, acid catalyst, H2O, stir evenly, and after sufficient hydrolysis, obtain silicon-based hydrolyzate; The particle size of the monodispersed silica sol in the ethanol solution is 15nm-45nm, and the solid content is 10%-30%; the acid catalyst is one of hydrochloric acid, oxalic acid, nitric acid, sulfuric acid, acetic acid, and hydrofluoric acid, the concentration of the acid catalyst solution is 0.01mol / L-0.8mol / L, and the solvent is anhydrous ethanol; wherein the mass ratio of silica sol, polyethyl silicate, acid catalyst, and H2O is 1:(0.02-1):(0.001-0.1):(0.20-1.5); S1-2, component B: mix anhydrous ethanol and concentrated ammonia water evenly to obtain an alkaline catalyst solution; wherein the weight ratio of anhydrous ethanol to concentrated ammonia water is 1:(0.002-0.08); S1-3, component C: After the organosilicon source, anhydrous ethanol and H2O are fully mixed, the acid catalyst is slowly added, the pH value of the solution is adjusted to 4.5-6, and a sunscreen is added. The mixture is evenly mixed by mechanical stirring + passing compressed air at the bottom of the container to obtain a mixed powder; The organic silicon source is one of ethyl orthosilicate, methyl orthosilicate, methyl triethoxysilane, methyl trimethoxysilane, and polyethyl silicate; wherein the weight ratio of the organic silicon source: anhydrous ethanol: H2O is 1: (10-20): (2-6); the sunscreen is one of silicon carbide, titanium dioxide, and zirconium oxide; the ratio of the sunscreen to the sol in component C is (0.5-3) kg: 100L, and the powder particle size is 1 μm-6 μm; the sol is organic silicon source + ethanol + H2O + inorganic acid; The pretreatment method of the mixed powder is: S1-3-1, rinsing: rinse with anhydrous ethanol 1 to 3 times; S1-3-2, surface treatment: hydroxylation or alkylation treatment is performed on the powder surface, and the powder is soaked in a surface treatment solution for 24 hours; The surface treatment solution is one of 1wt%-5wt% NaOH solution and 20wt%-50wt% methyl orthosilicate ethanol solution; S2: prepare a whole roll of fiber felt: width 0.5m-1.5m; The fiber felt is a blended felt of quartz fiber and ceramic fiber, and the volume fraction of quartz fiber in the total fiber is 5%-15%; S3: The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the components A, B and C are mixed in the pipeline at a volume ratio of 1:(2-8):(0.5-2) and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; S4: transporting the wet gel felt obtained in the above step to a microwave cavity through a transport line for microwave heating for rapid gelation and curing, and maintaining the temperature in the microwave cavity at 40° C.-60° C.; S5: aging the wet gel felt after leaving the microwave cavity at room temperature for 4h-12h; S6: adding ethanol to replace the wet gel felt after aging at room temperature; S7: After supercritical drying of the replaced wet gel felt, a low thermal conductivity, high temperature resistant silica aerogel insulation felt is obtained. The obtained low thermal conductivity, high temperature resistant silica aerogel insulation felt has the following properties: The maximum operating temperature reaches 1100℃, and the thickness shrinkage rate after treatment at 1100℃ for 1h is 0.20%-1.82%; The typical value of thermal conductivity at 800℃ is 0.048W / (m·K)-0.054W / (m·K), the typical value of thermal conductivity at 1000℃ is 0.066W / (m·K)-0.072W / (m·K), and the typical value of thermal conductivity at 1100℃ is 0.076W / (m·K)-0.085W / (m·K); Tensile strength is 0.32MPa-0.45MPa; The temperature of the cold side of a 30mm thick silica aerogel insulation felt heated at 1100℃ for 3600s is less than 200℃.

2. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt according to claim 1, characterized in that: The hydrolysis time in step S1-1 is 2h-8h.

3. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt according to claim 1, characterized in that: The uniform mixing in step S1-2 is carried out by stirring for 10-20 minutes.

4. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt according to claim 1, characterized in that: The mixing described in step S1-3 is uniform, and the stirring time is 2h-8h.

5. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt according to claim 1, characterized in that: The rapid gelation described in step S4 refers to a gelation time of 2 min to 6 min.

6. The method for preparing a low thermal conductivity, high temperature resistant silica aerogel insulation felt according to claim 1, characterized in that: The supercritical drying described in step S7 is CO2 supercritical drying or ethanol supercritical drying; the CO2 supercritical drying process is: the aerogel is protected by CO2 gas, the drying temperature is 40°C-75°C, the autoclave pressure is controlled to 8MPa-20MPa, and the reaction time is 4h-24h; the ethanol supercritical drying process is: the aerogel is protected by nitrogen gas, the drying temperature is 260°C-320°C, the autoclave pressure is controlled to 8MPa-14MPa, and the reaction time is 4h-10h.

7. A low thermal conductivity, high temperature resistant silica aerogel insulation felt, characterized by: The low thermal conductivity and high temperature resistant silica aerogel insulation felt is prepared by the method for preparing the same according to any one of claims 1 to 6, and has the following properties: The maximum operating temperature reaches 1100℃, and the thickness shrinkage rate after treatment at 1100℃ for 1h is 0.20%-1.82%; The typical value of thermal conductivity at 800℃ is 0.048W / (m·K)-0.054W / (m·K), the typical value of thermal conductivity at 1000℃ is 0.066W / (m·K)-0.072W / (m·K), and the typical value of thermal conductivity at 1100℃ is 0.076W / (m·K)-0.085W / (m·K); Tensile strength is 0.32MPa-0.45MPa; The temperature of the cold side of a 30mm thick silica aerogel insulation felt heated at 1100℃ for 3600s is less than 200℃.

Citation Information

Patent Citations

  • A method for preparing a high-temperature resistant aerogel composite material and the composite material thereof.

    CN114804819B

  • Preparation method of fiber felt enhanced silica aerogel composite panel

    CN104478394A

  • Method for preparing fiber-loaded rutile type TiO2 composite SiO2 aerogel

    CN106431186A